1988
DOI: 10.3382/ps.0670809
|View full text |Cite
|
Sign up to set email alerts
|

Feed Restriction in Broiler Breeder Pullets: Skip-a-Day Versus Skip-Two-Days

Abstract: Effects were compared of two methods of feed restriction (skip-a-day, SAD, vs. skip-two-days, STD) during 4 to 22 wk of age on the development, uniformity, and subsequent performance of White Rock pullets. The pullets, housed in cages, consumed the same amount of feed in both treatments. Nevertheless, body weights of birds kept under the STD feeding regimen were significantly (P less than .01) lower. This difference was still significant (P less than .05) at 35 wk of age. Flock uniformity at 11 wk of age was s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

1996
1996
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(11 citation statements)
references
References 16 publications
2
9
0
Order By: Relevance
“…The uniformity of female birds over the period (8 to 22 weeks) were within the breeder's acceptable level (80% or above) except at 20th weeks of age. The highest uniformity was found at 8th week (99%) but Bartov et al (1988) found higher uniformity at 11th week. The lowest uniformity was found at 20th week (69%) but Savory et al (1996) found poor uniformity in female breeder at 22 week of age.…”
Section: Uniformity Of Kasila Broiler Parent Chicksmentioning
confidence: 86%
“…The uniformity of female birds over the period (8 to 22 weeks) were within the breeder's acceptable level (80% or above) except at 20th weeks of age. The highest uniformity was found at 8th week (99%) but Bartov et al (1988) found higher uniformity at 11th week. The lowest uniformity was found at 20th week (69%) but Savory et al (1996) found poor uniformity in female breeder at 22 week of age.…”
Section: Uniformity Of Kasila Broiler Parent Chicksmentioning
confidence: 86%
“…Broiler breeders are the parent stock of broiler chickens and are expected to live for 60-70 weeks rather than just five. In addition to the high mortality rates, ad libitum-fed breeder hens reach sexual maturity too early and too heavy, requiring feed restriction from an early age both to remain physically healthy and to produce acceptable numbers of settable eggs (Bartov et al, 1988;Bruggeman et al, 1999). At the same time, the level of feed restriction required to maintain healthy breeding stock promotes hunger and frustration which creates an animal welfare trade-off known as the broiler breeder paradox (Decuypere et al, 2010).…”
Section: Rise Of the Modern Broilermentioning
confidence: 99%
“…The use of intermittent fasting (IF), or "skip-a-day", in broiler breeder rearing is supposedly the most common feed restriction regimen used globally in chicken production and is widely acknowledged to increase flock uniformity by increasing portion sizes, and thus feeding times, which reduces the amount of competition over feed (Bartov et al, 1988;Bennett and Leeson, 1989;Mench, 2002;Morrissey et al, 2014). Intermittent fasting has mostly been used in the form of alternate-day fasting, although fewer fasting days per week have been suggested from a welfare perspective (Renema and Robinson, 2004) and the use of two consecutive fasting days has also been tested (Bartov et al, 1988;Katanbaf et al, 1989). Generally speaking, however, IF in this context refers to fasting for no more than one consecutive day 1-4 times per week.…”
Section: Improving the Breeder Situation: Intermittent Fastingmentioning
confidence: 99%
See 1 more Smart Citation
“…The lighting regimen was 13 h lightll h dark. The chicks were fed a starter diet for breeder chicks (2,900 kcal/kg and 18.7% CP/kg) (Bartov et al, 1988), supplemented with 0.25% NaCl, and whose mineral mix supplied 50 mg Zn/kg diet. At the age of 1 wk, two-thirds of the chicks (those closest to the average weight) in Experiments 1 and 2, and all of them in Experiment 3, were wing-banded and divided into groups of 10 chicks each.…”
Section: Introductionmentioning
confidence: 99%